(3LhGH GHf SjfG cJGH JdejPg CHj YHjO GdLhRLGfjs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3HYO GdHSedI hGdOjHGLI hUdJ GdeSCdI hGdeYGhOI ai GdfaS hhbaJ GdCf Ydi ZQVg ajgG hUGObJg dYdg de jJCed eG bdJg ai GdLhGH GdChd JCedkG s
(3BNQgG (B:s
(3aGdeecf HGdeYfj GdChd eeJfY ai HYV GdCMjGA s
(3Vef eLehY , JQJjHgG (B: 9s
(3hjJdhgG QbY ef cdGe GHf SjfGs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3eJaQbGJs